Investigation of optical properties of metal-doped CsPbX3 perovskite nanocrystals - V.P. Bezverkhniy; A.Y. Gagarina; E.N. Muratova; A.I. Maximov; V.A. Moshnikov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
As a part of the research work, inorganic lead-containing halide perovskite nanocrystals with the CsPbX3 structure were obtained by the hot injection. The alloying of single crystals of perovskites was carried out by solution methods, zinc and indium ions acted as dopants. The photoluminescence spectra and optical density spectra of the obtained colloidal solutions were studied. Our studies have shown that doping of perovskite nanocrystals with metal ions leads to an increase in photoluminescence as well as to a shift in the maximum of photoluminescence relative to the reference composition by 4 and 12 nm for bromides and iodides, respectively. Also, it has been shown that the magnitude of the shift does not depend on the type of dopant. It is noted that within the framework of this work, doping does not lead to a change in the position of the edge of its own absorption.